问题
解答题
|
答案
(1)
÷3+1 5
×4 5
,1 3
=
×1 5
+1 3
×4 5
,1 3
=(
+1 5
)×4 5
,1 3
=1×
,1 3
=
,1 3
(2)
÷1 3
+4 9
+1 3
,1 4
=
×1 3
+9 4
+1 3
,1 4
=
+3 4
+1 4
,1 3
=1+
,1 3
=1
,1 3
(3)(
-4 5
) ×2 3
,25 2
=
×4 5
-25 2
×2 3
,25 2
=10-
,25 3
=1
,2 3
(4)3-
×3 2
-10 21
,2 7
=3-
-5 7
,2 7
=3-(
+5 7
),2 7
=3-1,
=2,
(5)
÷【(1 5
+2 3
)×1 5
】,1 13
=
÷【1 5
×13 15
】,1 13
=
÷1 5
,1 15
=3,
(6)24×
,4 25
=(25-1)×
,4 25
=25×
-1×4 25
,4 25
=4-
,4 25
=3
,21 25
(7)【4-(
-3 4
)】×3 8
,4 29
=【4-
】×3 8
,4 29
=
×29 8
,4 29
=
,1 2
(8)26×
,4 25
=(25+1)×
,4 25
=25×
+1×4 25
,4 25
=4+
,4 25
=4
,4 25
(9)
+1 7
×7 8
+5 7
,3 8
=
+ (1 7
+5 8
),3 8
=
+ 1,1 7
=1
,1 7
(10)
+(1-1 4
-1 2
),1 4
=
+1 4
,1 4
=
.1 2